Polydopamine/puerarin nanoparticle-incorporated hybrid hydrogels for enhanced wound healing. (8th August 2019) - Zhang, Shaohan; Ou, Qianmin; Xin, Peikun; Yuan, Qijuan; Wang, Yan; Wu, Jun
Abstract : Oxidative damage generated would disrupt the oxidant/antioxidant balance in cells, causing slow wound healing and tissue regeneration. Hydrogel dressing with antioxidant properties can promote wound healing, however, its design is still a challenge. Abstract : Oxidative damage generated by various biochemical pathways can disrupt the oxidant/antioxidant balance in cells, causing slow wound healing and tissue regeneration; in this regard, a hydrogel dressing with antioxidant properties can promote wound healing; however, its design is still a challenge. Herein, a polydopamine/puerarin (PDA/PUE) nanoparticle-incorporated polyethylene glycol diacrylate hybrid hydrogel (PEG-DA/PDA/PUE) with antioxidant properties was prepared and used as a wound-healing material. Experimental observations indicated that the PEG-DA/PDA/PUE hydrogel possessed excellent swelling capacity and mechanical property. Moreover, the antioxidant capability was enhanced with an increase in the concentration of polydopamine/puerarin nanoparticles in the hydrogel. The hydrogel presented good cell proliferation and antioxidant activity, including a decrease in ROS and increase in the superoxide dismutase (SOD) and glutathione peroxidase (GPx) activity under oxidative stress conditions. Furthermore, the full-thickness skin-defect-regeneration process could be accelerated via the antioxidant hydrogel treatment. This study validated the potential applications of an antioxidant hydrogel for wound healing.